Effect of Citrus aurantium l. essential oil on muscle regeneration in mdx mice - Tome de Souza, Paula Aiello [UNESP]; Marques, Maria Julia; Hiruma-Lima, Clélia Akiko [UNESP]; Michelin Matheus, Selma Maria (Soc Chilena Anatomia, 2011)
Duchenne muscular dystrophy (DMD) is a severe X-linked recessive disorder characterized by the progressive loss of muscular strength. Mdx mutant mice show a marked deficiency in dystrophin, which was related to muscle membrane stability. The aim of this study was to verify the possible protective anti-inflammatory effect of citrus oil on mdx muscle fibers. Thus, adult male and female mdx mice (014/06-CEEA) were divided into control and citrus-treated. After 60 days of treatment, one ml of blood was collected for creatine kinase (CK) test. Diaphragm, sternomastoideus, anterior tibial and gastrocnemius muscles were removed and processed according to histological routine methods. The observed alterations indicate a direct effect of citrus. Recent studies have improved the diagnosis of muscular diseases but with no definitions of efficient treatments. Intervention with several therapies is important to many patients presenting muscular dystrophy, which enables them to live longer and be more active, while there is no development of gene therapies.

La distrofia muscular de Duchenne (DMD) es una enfermedad grave ligada al cromosoma X, trastorno recesivo que se caracteriza por la pérdida progresiva de fuerza muscular. Mdx ratones mutantes muestran una marcada deficiencia en la distrofina, que está relacionada con la estabilidad de la membrana muscular. El objetivo de este estudio fue comprobar el posible efecto protector, antiinflamatorio del aceite de cítricos en las fibras musculares mdx. Los ratones mdx adultos machos y hembras (014/06-CEEA) se dividieron en control y cítricos tratados. Después de 60 días de tratamiento, un ml de sangre fue recogida para cuantificar la creatina quinasa (CK) de prueba. Fueron retirados y procesados los músculos diafragma, esternomastoideo, tibial anterior y gastrocnemio de acuerdo con los métodos de rutina histológica. Las alteraciones observadas indican un efecto directo de los cítricos. Estudios recientes han mejorado el diagnóstico de enfermedades musculares, pero sin definiciones de tratamientos eficaces. Intervención con varias terapias es importante para muchos pacientes que presentan distrofia muscular, lo que les permite vivir más y ser más activos, mientras no exista desarrollo de terapias génicas.
Efecto del aceite esencial de Citrus aurantium l. en la regeneración muscular en ratones mdx
Keywords: Muscle fiber; Duchenne muscular dystrophy; Citrus aurantium L.; mdx mouse; Muscle regeneration; Central nuclei